2018
DOI: 10.1177/1359105318793182
|View full text |Cite
|
Sign up to set email alerts
|

Go with the FLOW: Implementation of a psychological skills intervention in an exercise program for post-bariatric surgery patients

Abstract: Bariatric surgery is an effective obesity treatment; however, most individuals regain weight following surgery. Following a Lifestyle of Wellness (FLOW) is a psychological skills intervention with strategies designed to increase self-efficacy and promote living a healthy lifestyle including regular physical activity. Eleven participants completed FLOW. Results indicated participants enjoyed the program and intended to continue this lifestyle upon program completion. Interviews indicated FLOW was effective for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…In this study, participants experienced flow states while performing the exercises, so it can be assumed that they adapted to the difficulty of the challenge and felt a sense of mastery. This is supported by research that suggests that flow is related to the balance between an individual's athletic and psychological abilities [36].…”
Section: Comparison To Prior Workmentioning
confidence: 85%
“…In this study, participants experienced flow states while performing the exercises, so it can be assumed that they adapted to the difficulty of the challenge and felt a sense of mastery. This is supported by research that suggests that flow is related to the balance between an individual's athletic and psychological abilities [36].…”
Section: Comparison To Prior Workmentioning
confidence: 85%
“…suitable for studying consumer-based brand equity by identifying relevant "character traits" which may assist the optimization of current processes [35]. In the context of BS, Powell et al showed that psychological skills interventions can be implemented successfully to improve postbariatric patients' participation in exercise programs [36]. Consequently, the network-based map of associations to weight loss presented in this study may serve as a navigational tool for caregivers, policy actors and researchers to better identify patients' implicit interest toward weight loss and to design new interventions aiming to tackle mindset barriers in the acceptance of BS among patients with obesity [37].…”
Section: Discussionmentioning
confidence: 99%
“…Los esfuerzos gubernamentales para frenar el aumento de la población obesa a pesar de ser vanguardistas han mostrado tímidos resultados, sin impacto positivo sobre la morbilidad general, ni sobre el gasto en salud pública; esta problemática va más allá del ámbito clínico, generando un impacto negativo sobre la calidad de vida y predisponiendo a la discriminación social, tornando conflictivas las relaciones interpersonales [2][3][4][5][6][7]. Existen diversas opciones y esquemas de tratamiento para la obesidad, que involucran la modificación de la conducta alimentaria, actividad física, soporte psicológico y/o soporte farmacológico con resultados visibles a corto plazo, pero limitados o inefectivos a largo plazo, dando paso al tratamiento quirúrgico [8][9][10]. Implementada en los años 60, la cirugía bariátrica se lleva a cabo en la actualidad mediante técnicas de mínima invasión y constituye una opción efectiva de tratamiento para la obesidad, sin limitar su beneficio a esta patología, pues otorga buenos resultados en cuanto a control y/o remisión de enfermedades asociadas, constituyendo un adyuvante en la reducción de la mortalidad general [11][12][13].…”
Section: Introductionunclassified